1999
DOI: 10.1139/y99-064
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of combined terlipressin and tetramethylpyrazine administration on portal hypertensive rats

Abstract: The purpose of this study was to investigate the therapeutic effects of terlipressin (TP) alone or in combination with tetramethylpyrazine (TMP) on anesthetized portal hypertensive rats. Portal hypertension was induced by either partial portal vein ligation (PVL, without cirrhosis) or bile duct ligation (BDL, with cirrhosis) in Sprague-Dawley rats. Each PVL or BDL rat received only one of the two regimens: vehicle for 3 min followed by TP (0.017 mg x kg(-1) x min(-1) for 3 min) or TMP (10 mg x kg(-1) x min(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Pyrazine volatiles are mostly responsible for roasted, nutty, caramel and similar aroma/flavor descriptions . In addition, 2,3,5,6‐tetramethylpyrazine (TMP) is a biologically active ingredient that has been found to have significant therapeutic activity, including improving brain microcirculation, inhibiting thrombus formation, decreasing platelet aggregation and improving blood viscosity . It was reported recently that TMP has appreciable blood–brain barrier (BBB) penetrability …”
Section: Resultsmentioning
confidence: 99%
“…Pyrazine volatiles are mostly responsible for roasted, nutty, caramel and similar aroma/flavor descriptions . In addition, 2,3,5,6‐tetramethylpyrazine (TMP) is a biologically active ingredient that has been found to have significant therapeutic activity, including improving brain microcirculation, inhibiting thrombus formation, decreasing platelet aggregation and improving blood viscosity . It was reported recently that TMP has appreciable blood–brain barrier (BBB) penetrability …”
Section: Resultsmentioning
confidence: 99%
“…Common bile duct ligation was performed in male Sprague-Dawley rats (250-300 g) to induce hepatic fibrosis and portal hypertension (Kountouras et al 1981), as previously described (Chang et al 1999). Rats were anesthetized with ether.…”
Section: Bile Duct Ligated (Bdl) Ratsmentioning
confidence: 99%
“…In our previous study, Zhenjiang aromatic vinegar was found to possess antioxidant activity, which was due to the common action of flavonoids, polyphenols, amino acids and organic acids, as well as ligustrazine (2,3,5,6‐tetramethylpyrazine) and melanoidins 6–8. Among these compounds, ligustrazine, which is a bioactive alkaloid originally isolated from the traditional Chinese medicine Ligusticum chuanxiong Hort., has attracted much public interest because of its potent bioactivities, such as curing cardiovascular and cerebrovascular diseases and hypertension 9–11…”
Section: Introductionmentioning
confidence: 99%